2006
DOI: 10.1074/jbc.m603508200
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Deletion of Rac1 GTPase Reveals Its Critical Role in Actin Stress Fiber Formation and Focal Adhesion Complex Assembly

Abstract: Rac1 is an intracellular signal transducer regulating a variety of cell functions. Previous studies by overexpression of dominant-negative or constitutively active mutants of Rac1 in clonal cell lines have established that Rac1 plays a key role in actin lamellipodia induction, cell-matrix adhesion, and cell anoikis. In the present studies, we have examined the cellular behaviors of Rac1 gene-targeted primary mouse embryonic fibroblasts (MEFs) after Cre recombinase-mediated deletion of Rac1 gene. Rac1-null MEFs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
125
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(157 citation statements)
references
References 52 publications
29
125
2
1
Order By: Relevance
“…The involvement of Rac3 in cellsubstrate adhesion during cell invasion is a novel finding in this study. Although the molecular mechanism by which Rac regulates cell-substrate adhesion remains unknown, it has been reported that Rac1 depletion suppresses focal complex formation in embryonic fibroblasts and carcinoma cells (Guo et al, 2006;Yip et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of Rac3 in cellsubstrate adhesion during cell invasion is a novel finding in this study. Although the molecular mechanism by which Rac regulates cell-substrate adhesion remains unknown, it has been reported that Rac1 depletion suppresses focal complex formation in embryonic fibroblasts and carcinoma cells (Guo et al, 2006;Yip et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings indicate that Rac1 may play an important role in the carcinogenesis and progression of gastric carcinoma, because increased Rac1 expression was related to higher TNM stages. 22 Genetic deletion of Rac1 has revealed its critical role in cell survival regulation 23 suggesting that increased expression of Rac1 in tumors may protect cells from apoptosis and lead to an increase of cellmatrix-interaction and cell spread. However, despite these important functions that are attributed to Rac1, no association of expression of Rac1 with prognosis was found in our study of gastric carcinomas.…”
Section: The Rho Gtpase Rac1mentioning
confidence: 99%
“…DN-Rac-1 and -Cdc42 expression inhibit cell spreading in NIH3T3 cells on several substrates [38] and Rac-1 deficiency in fibroblasts causes cell rounding on fibronectin. [19,27] Further, Rac-1 activation in endothelial cells induces spreading, even in integrin kinase deficient cells. [39] RhoA, as well as Rac-1, has strong effects on the reorganization of cytoskeletal structures and thus, directs changes in cell shape in various cell types that grow in an anchorage dependent manner.…”
Section: Chondrocyte Morphologymentioning
confidence: 99%
“…[20,27] Thus, we first determined the ability of Rac-1 to modulate cell attachment and spreading. The infected chondrocytes were plated on collagen type I, fibronectin, gelatin, or collagen type II substrates and cell attachment was quantified by computer-assisted analysis one hour after plating.…”
Section: Effects Of Ca-and Dn-rac-1 On Cell Adhesion and Spreadingmentioning
confidence: 99%